Fast 3-D millimeter-wave MIMO array imaging algorithms based on the CF-DFrFT - Li, Qirun; Li, Xinbo; Chen, Ziyi; Jiang, Liangxu; Wang, Yingwei (Digital signal processing, 2024)
In near-field applications, 3-D imaging with the millimeter-wave multiple-input-multiple-output (MIMO) array provides accurate reconstruction with high dynamic range. However, current algorithms make it difficult to process multidimensional echo data in real-time with ordinary computational power. To improve the imaging speed, the property of the focus position control by closed-form discrete fractional Fourier transform (CF-DFrFT) is used to replace the matched filtering operation. According to the difference of range cell migration correction (RCMC), three improved imaging algorithms based on the CF-DFrFT are proposed in this article. We numerically analyze the CF-DFrFT of different imaging algorithms in terms of imaging computational load and feasibility. The imaging difference is also discussed using simulated data and published actual data. Compared to the fastest known algorithm, the simulation results show that the imaging time of the proposed algorithms is reduced by 38% at most. All the proposed algorithms improve the imaging efficiency while preserving the properties of the original RCMC.